Implementasi Pembelajaran Berbasis Etnosains Terhadap Hasil Belajar Ipa Siswa Madrasah Tsanawiyah Negeri Di Kota Palu - Mirnawati Mirnawati (Lembaga Bale Literasi, 2026)
This study aims to reveal the differences in the learning outcomes of students who implement ethnoscience-based science learning and conventional learning at Madrasah Tsanawiyah Negeri in Palu City. Using a quantitative approach, the technique of collecting data through tests. The data analysis techniques used were validity tests, and classical assumption tests, namely normality tests, homogeneity tests, and hypothesis tests. This research was conducted in four Madrasah Tsanawiyah schools in Palu City, namely MTsN 1 Palu, MTsN 2 Palu, MTsN 3 Palu and MTsN 4 Palu. Each school took 2 sample classes in grade VII. 4 experimental classes and 4 control classes. The number of respondents was 196 people. The data processing of this research uses the Jamovi application version 2.3.28. The results of the study show that the learning outcomes of science in classes that implement ethnoscience-based learning are different from conventional classes. It is characterized by the results of a statistical test (t-test), namely with a sig value of 0.001 < 0.05 so that Ha is accepted, namely there is a difference in science learning outcomes in classes that implement ethnoscience-based learning compared to conventional classes. The results of the correlation analysis showed that r of 0.447 indicated the degree of relationship between learning outcomes and the value of student learning outcomes at a moderate level. From the results of the t-test, an effect size value of 54.8% was also obtained, which shows how much the implementation of ethnoscience-based science learning has influenced the value of scientific learning outcomes. The implication of this research is that the results of this research are expected to contribute to thinking to always include cultural elements in every learning. So that schools in Palu City, especially for Madrasahs, will have characteristics that enrich insights for their students. It is also expected to be one of the contributions of thinking to make policies related to the school curriculum to pay more attention to local wisdom.